ANALISIS FAKTOR KEPESERTAAN PROGRAM JAMINAN KESEHATAN NASIONAL DI KABUPATEN AGAM - Hilma Shofia; Jihan Putri Ralya; Indah Cahyani; Fitriani Pramita Gurning (Jurnal Penelitian Kesmasy, 2023)
The Social Security Administering Body (BPJS) is a legal entity established as the administering body for the health insurance program. In this case, social security has been designed as a form of social protection, in order to provide guarantees to all people so that they can fulfill their basic needs for a more decent life. Based on the data found, it stated that as many as 453,185 (86.35%) of the people of the Agam district had been recorded as member BPJS with the entire Agam Regency community totaling 524,829. However, this coverage is still categorized as low because it has not yet reached Universal Health Coverage (UHC) coverage at number 95% and for the district government of Agam itself is targeting the membership of the national health insurance in Agam district to reach 100 percent. This research technique uses qualitative research methods and data collection through interviews, where the interview process was carried out by an oral debriefing process that took place in one direction. The interview process is carried out by asking questions to the informants regarding the title of the research and later the informants will give their answers. Got the results in this study state that there are several factors for community participation in participating in the National Health Insurance program, including: Interest, Obedience, Social Effect, Warranty, and Experience.